Persepsi Generasi Milenial dan Generasi Z tentang Pernikahan - Dewi Rosa; Yeni Afrida (Lembaga Yasin AlSys, 2026)
Shifts in perceptions of the institution of marriage among Millennials and Generation Z have become increasingly pronounced alongside social, economic, technological, and cultural changes. This study aims to comparatively analyze the perceptions, values, future expectations, and challenges of both generations in understanding and navigating marriage in Lubuk Kupang Urban Village, Lubuklinggau City. The study employed a qualitative approach with a comparative descriptive design. Informants were selected using purposive sampling based on data saturation and comprised eight primary informants, namely four Millennials and four members of Generation Z, as well as one supporting informant from the urban village administration. Data were collected through semi-structured in-depth interviews and documentation studies and were subsequently analyzed interactively through data reduction, data presentation, and conclusion drawing. Data credibility was established through source and technique triangulation. The findings indicate that Millennials view marriage from a pragmatic-realistic perspective, emphasizing emotional readiness, economic stability, and moral and spiritual foundations. In contrast, Generation Z views marriage from a pragmatic-calculative perspective, emphasizing risk mitigation, individual autonomy, mental health, and career independence. Despite their different orientations, both generations emphasize the importance of egalitarian partnerships, financial transparency, and the rejection of costly traditional wedding celebrations. These findings affirm that delaying marriage is regarded as a protective and proactive strategy for supporting household sustainability. This study formulates the Adaptive Rational-Risk Partnership Theory, which positions psychological maturity, financial stability, and partnership equality as the principal pillars of modern family resilience.